SORTING TECHNIC OF TRADITIONAL MARKET WASTE IN MAGELANG CITY - Ayu Rahayu; Adhi Surya Perdana (Journal of Livestock Science and Production, 2018)
AbstractThe city of Magelang is a city that has a large population. Due to the automatic density of the population, there will be many shopping places, one of which is the market to meet the daily needs of the community. Magelang city is able to produce market waste up to 300 tons per day. The waste has not been used properly. This can cause environmental pollution. Market waste in the city of Magelang is a homework that must be immediately completed because all this time it has not been fully processed. The research objective is to sort out organic and inorganic waste at the Koa Market in Magelang. The sample of research includes five markets namely Rejowinangun, Gotong Royong, Kebonpolo, Cacaban and Sidomukti. The research method used survey method with questionnaire research tool aimed at market traders to know the characteristics of market traders, merchant waste, average amount of waste and its utilization, and other supporting components. Presentation of data analysis result obtained by descriptive analysis approach. Field findings of the average amount of market waste volume that can be utilized as livestock feed per m3/day based on market location that is Rejowinangun Market (9,2 m3), Gotong Royong (5,2 m3), Kebonpolo (3,3 m3) Cacaban (1.8 m3), and Sidomukti (2.1 m3), it is expected that this research can be used as a reference for market waste treatment in determining the policy of the local Industry and Trade Office. Keywords: Sorting technique, Waste Traditional Market, Magelang